Resident's water accessibility towards sustainability: The case of informal settlements of JOS Metropolis, Nigeria - Veronica Yilret Nanle; Normah Abdul Latip; Rehmat Karim (Malaysia Institute of Planners, 2022)
This study is aimed at determining the type of relationship that exists among variables that affect informal residents access to water in the study area. A structured closed ended questionnaire was prepared and administered to a sample of 382 respondent’s, mostly women and girls in five informal settlements of Jos Metropolis. Results from the study revealed that the β and p values of the predictors are as follows; cost and affordability (β=0.113, p=0.014), Intermittent water supply (β =0.045, p -0.190, Physical distance (β=0.365, p<0.001) and lastly Queuing for water (β=0.151, p=0.002). Out of the four-hypothesis developed, cost and affordability, physical distance and queuing for water have a significant negative effect on resident’s access to water. This study therefore contributes a significant gap in methodology by determining the relationship among variables, using PLS-SEM for regression analysis, which is entirely a different method from what was used in previous studies. Hence, presents the novelty of this study.